2021
DOI: 10.1080/14658011.2021.1890515
|View full text |Cite
|
Sign up to set email alerts
|

Facile fabrication of NiAl-LDH and its application in TPU nanocomposites targets for reducing fire hazards

Abstract: In this study, nickel-aluminium layered double hydroxide (NiAl-LDH) was prepared and characterised. NiAl-LDH was incorporated into thermoplastic polyurethane (TPU) to prepare a series of TPU/NiAl-LDH nanocomposites using solution mixing technology. Thermogravimetric analysis revealed that the addition of NiAl-LDH increased the thermal stability of TPU/NiAl-LDH nanocomposite at high temperatures. Kinetic analysis of the nanocomposites was conducted via the Coats-Redfern method. Thermogravimetric infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 67 publications
1
8
0
Order By: Relevance
“…Figure 4 exhibits the TG and DTG curves of TPU, TPU/AHP and TPU/AHP/MIT composites, and the relevant data are given in Table 3. It can be seen from Figure 4a that both TPU and flame retardant TPU composites exhibit two degradation stages, corresponding to the thermal decomposition of hard and soft segments in PU molecular chain 47 . Table 3 shows that T −5% of TPU/AHP25 decreases to 286°C with T − 50% increases to 386°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 exhibits the TG and DTG curves of TPU, TPU/AHP and TPU/AHP/MIT composites, and the relevant data are given in Table 3. It can be seen from Figure 4a that both TPU and flame retardant TPU composites exhibit two degradation stages, corresponding to the thermal decomposition of hard and soft segments in PU molecular chain 47 . Table 3 shows that T −5% of TPU/AHP25 decreases to 286°C with T − 50% increases to 386°C.…”
Section: Resultsmentioning
confidence: 99%
“…Figure4exhibits the TG and DTG curves of TPU, TPU/AHP and TPU/AHP/MIT composites, and the relevant data are given in Table3. It can be seen from Figure4athat both TPU and flame retardant TPU composites exhibit two degradation stages, corresponding to the thermal decomposition of hard and soft segments in PU molecular chain 47. Table3shows that T À5% of TPU/AHP25 decreases to 286 C with T À50% increases to 386 C. It is also observed that T max of TPU/AHP25 in the first stage is declined to 313 C, which is due to PH 3 afford by AHP decomposition is a Lewis acid, which can promote the decomposition of -NCO into C-N bonds and benzene rings, and accelerate the decomposition of PU molecular chains 48,49.…”
mentioning
confidence: 99%
“…The Coats-Redfern method applies to the main degradation region of the material, and kinetic parameters such as E and A can be calculated. 17 Figure 4 showed the linear relationship between lng(x)T2 and 1T of TPU and TPU/MIT composites with different n values, and the corresponding data were shown in Table 4. It could be seen from Figure 4 that the correlation of various fitting lines as well, indicating that the Coats-Redfern method was feasible.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed that the Ti 3 C 2 T x /Nano-Cu heterocycles exhibited strong interfacial interactions with the TPU host, and the CO production rate of the corresponding TPU composites was much lower than that of the pure TPU when 2 wt% of Ti 3 C 2 T x /Nano-Cu was added. Liu et al 17 prepared nickel-aluminum bimetallic hydroxide(NiAl-LDH) and used it to flame retardant TPU. It was shown that the addition of 3 wt% NiAl-LDH increased the residual carbon rate of TPU/NiAl-LDH nanocomposites from 0.1 wt% to 2.6 wt% at 700 o C, meanwhile NiAl-LDH could effectively improve the stability and graphitization of carbon layer for the TPU composites, thereby improving the fire safety performance of the composites.…”
Section: Introductionmentioning
confidence: 99%
“…As discussed above, LDH nanosheets and DOPO nanoparticles synergistically facilitate the formation of char residue, and the structure of the protective char layer is critical to the flame retardancy of EP composites. 45,46 Digital photos of char residues from various EP composites are shown in Figure S7. Consistent with the TGA results, neat EP (Figure S7a) gives the smallest char yield after combustion compared with the flame-retardant-treated EP composites (Figure S7b−e), and the scattered carbon residues are not connected into a continuous carbon layer.…”
Section: Char Residue Analyses Of Flame Retarding Ep Compositesmentioning
confidence: 99%